HOAX SERBUAN TKA DARI CHINA: KEPANIKAN MORAL DAN BUDAYA KETAKUTAN - Triyono Lukmantoro (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2018)
At the end of December 2016, the hoaxes emerged stating that there were about ten million, even twenty million, illegal foreign workers from China who were invading Indonesia. Although the hoaxes have been strongly denied and regarded as slander by the government, in fact, the hoaxes were already spreading. One of the sites that produce these hoaxes is Postmetro. This article is a textual review of various hoax titles displayed by Postmetro. The results of this study show that the various hoaxes are no more the practices of